Automatic program reports - Lígia Maria da Silva Ribeiro (2007)
To profit from the data collected by the SIGARRA academic IS, a systematic setof graphs and statistics has been added to it and are available on-line. Thisanalytic information can be automatically included in a flexible yearly report foreach program as well as in a synthesis report for the whole school. Somedifficulties in the interpretation of some graphs led to the definition of new keyindicators and the development of a data warehouse across the university whereeffective data consolidation is obtained.